Screening for anaemia: evaluation of a haemoglobinometer. Issue 10 (October 1989) - Mills, A F; Meadows, N
Abstract : The HemoCue haemoglobinometer was evaluated as part of a programme to screen children aged 11-36 months for anaemia when they attended a routine immunisation clinic. Paired capillary blood samples were collected and measured on the haemoglobinometer and on a Coulter counter model S. Measurements made from bottle collected capillary samples were more precise than those made from single drops of blood. After compensation for a fixed bias the haemoglobinometer had a sensitivity of 0.85 and a specificity of 0.94 when used to detect anaemia. Careful attention must be paid to the method of blood collection. We suggest that cuvettes are filled from bottle collected capillary samples rather than single blood droplets taken direct from the finger. The haemoglobinometer was reliable, simple to use with the minimum of training, and proved to be suitable for use in a community child health clinic.